Pengaruh Liveworksheets Berbasis Discovery Learning Terhadap Hasil Belajar Tematik Terpadu Siswa Sekolah Dasar - Lusi Afriani; Reinita Reinita (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
This study's goal was to determine how Liveworksheets LKPD, which are based on Discovery Learning, affected the learning outcomes of Class V students at SDN 27 Pasar Kambang. This study uses the quasi-experimental approach and is quantitative in nature. The Non-equivalent Group Design was used in this investigation. Every fifth grader at SDN 27 Pasar Kambang makes up the population in the study. Two sample classes, Class VB as the experimental group and Class VA as the control group, were collected using a cluster random sampling approach. For this investigation, the t test will be used to assess the hypothesis data. Calculated using the t-test,  >  equals 2.14 > 2.017. Therefore, it can be said that there is an influence on the use of Discovery Learning-based LKPD Liveworksheets on learning outcomes of integrated thematic learning outcomes in elementary schools. That is, if the teacher uses the discovery learning model and uses worksheets based on live worksheets it is proven to be able to improve student learning outcomes.